PEMAHAMAN TENTANG MAKNA KETAATAN BERIBADAH BERDASARKAN IBRANI 10:22-25 - Darwis Lodowich Laana; Suryowati Wang (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2023)
Worship is a privilege for believers, in which Jesus himself is the intermediary between man and God. Obedience of worship is a must as an expression of gratitude and obedience to Allah. However, at this time worship is no longer something that is considered sacred but is only limited to routines where the congregation gathers and worships without understanding the true meaning of worship. This study aims to provide answers regarding the meaning of obedience and worship How understanding of the meaning of worship based on Hebrews 10: 22 – 25. This research uses the literature review method which is a systematic method followed by exegesis. The results of the study show that obedience to worship is an attitude of obedience and a sign of respect in humbling oneself as an expression of gratitude to God and; the meaning of worship in Hebrews 10:22-25 consists of facing God, holding fast to the confession of hope, caring for one another and advising one another.